Comparison of responses of human melanoma cell lines to MEK and BRAF inhibitors - Stones, Clare J.; Kim, Ji Eun; Joseph, Wayne R.; Marshall, Elaine S.; Leung, Euphemia; Finlay, Graeme J.; Shelling, Andrew N.; Baguley, Bruce C. (Frontiers in Genetics, 2013)
The NRAS and BRAF genes are frequently mutated in melanoma, suggesting that the NRAS-BRAF-MEK-ERK signalling pathway is an important target for therapy. Two classes of drugs, one targeting activated BRAF and one targeting MEK, are currently undergoing clinical evaluation. We have analysed the NRAS and BRAF mutational status of a series of 44 early passage lines developed from New Zealand patients with metastatic melanoma. 41% of the lines analysed had BRAF mutations, 23% had NRAS mutations and 36% had neither. We then determined IC50 values (drug concentrations for 50% growth inhibition) for CI-1040, a commonly used inhibitor of MEK kinase; trametinib, a clinical agent targeting MEK kinase; and vemurafenib, an inhibitor of mutant BRAF kinase. Cell lines with activating BRAF mutations were significantly more sensitive to vemurafenib than lines with NRAS mutations or lines lacking either mutation (p < 0.001). IC50 values for CI-1040 and trametinib were strongly correlated (r = 0.98) with trametinib showing ~100-fold greater potency. Cell lines sensitive to vemurafenib were also sensitive to CI-1040 and trametinib, but there was no relationship between IC50 values and NRAS mutation status. A small number of lines lacking a BRAF mutation were sensitive to CI-1040 but resistant to vemurafenib. We used western blotting to investigate the effect on ERK phosphorylation of CI-1040 in four lines, of vemurafenib in two lines and of trametinib in two lines. The results support the view that MEK inhibitors might be combined with BRAF inhibitors in the treatment melanomas of with activated BRAF. The high sensitivity to trametinib of some lines with wild-type BRAF status also suggests that MEK inhibitors could have a therapeutic effect against some melanomas as single agents.